Obsidian pyroclasts in the Yellowstone-Snake River Plain ignimbrites are dominantly juvenile in origin - L. R. Monnereau; B. S. Ellis; D. Szymanowski; O. Bachmann; M. Guillong (Bulletin of Volcanology, 2021)
Dense, glassy pyroclasts found in products of explosive eruptions are commonly employed to investigate volcanic conduit processes through measurement of their volatile inventories. This approach rests upon the tacit assumption that the obsidian clasts are juvenile, that is, genetically related to the erupting magma. Pyroclastic deposits within the Yellowstone-Snake River Plain province almost without exception contain dense, glassy clasts, previously interpreted as hyaloclastite, while other lithologies, including crystallised rhyolite, are extremely rare. We investigate the origin of these dense, glassy clasts from a coupled geochemical and textural perspective combining literature data and case studies from Cougar Point Tuff XIII, Wolverine Creek Tuff, and Mesa Falls Tuff spanning 10 My of silicic volcanism. These results indicate that the trace elemental compositions of the dense glasses mostly overlap with the vesiculated component of each deposit, while being distinct from nearby units, thus indicating that dense glasses are juvenile. Textural complexity of the dense clasts varies across our examples. Cougar Point Tuff XIII contains a remarkable diversity of clast appearances with the same glass composition including obsidian-within-obsidian clasts. Mesa Falls Tuff contains clasts with the same glass compositions but with stark variations in phenocryst content (0 to 45%). Cumulatively, our results support a model where most dense, glassy clasts reflect conduit material that passed through multiple cycles of fracturing and sintering with concurrent mixing of glass and various crystal components. This is in contrast to previous interpretations of these clasts as entrained hyaloclastite and relaxes the requirement for water-magma interaction within the eruptive centres of the Yellowstone-Snake River Plain province.